ЖИЗНЕННЫЙ ЦИКЛ СЛИЗНЕЙ - Turkomilax (Michaelis) natalianus (Michaelis,1892) и Deroceras (Deroceras) sturanyi (Simroth, 1894) ((Mollusca, Gastropoda) В УСЛОВИЯХ ЗАИЛИЙСКОГО АЛАТАУ (Experimental biology, 2009)
In the conditions of Ili of Alatau is studied the life cycle of Turkomilax (Michaelis) natalianus (Michaelis,1892) and Deroceras (Deroceras) sturanyi (Simroth, 1894).
Keywords: life cycle; sturanyi